Pengembangan Perangkat Pembelajaran Berbasis Proyek Materi Zakat, Infaq, Sedekah, dan Wakaf terhadap Hasil belajar pada Mata Kuliah Pendidikan Agama Islam Fakultas Ekonomi dan Bisnis Universitas Negeri Gorontalo - Kholid Mootalu; Agil Bahsoan; Muhammad Fakhri Mudi (Ideas Publishing, 2026)
This study aims to develop a learning device that integrates a project-based approach on the topic of Zakat, Infaq, Sedekah, and Wakaf (ZISWAF) in the Islamic Education. The method used in this study is Research and Development (R&D) analysis, which includes the stages of needs, device design, validation by experts, product revision, limited trials, and small-scale implementation. The results of the study obtained The validity of the learning device was obtained through expert assessment, resulting in a validity percentage of 88.26% with the criteria